ANÁLISIS MULTICRITERIO Y SELECCIÓN INTERACTIVA DEL USO AGRARIO DE AGUAS RESIDUALES TRATADAS, ADELIA MARÍA, CÓRDOBA, ARGENTINA - D. de Prada, Jorge; Degioanni, Américo J.; Cisneros, José M.; Gil, Horacio A.; Plevich, Omar J.; Chilano, Yanina; Pereyra, Cecilia I.; Cantero, Alberto (European Scientific Journal, ESJ, 2014)
We present a method for ranking agricultural alternatives of using treated wastewater, and interacting with decision makers of the cooperative Adelia Maria, Cordoba, Argentina for choosing the best alternative. Five alternatives (Eucalyptus, Poplar, Alfalfa, Wheat-Corn and Pinus with alfalfa) for using future 251.000m3 year -1 of treated wastewater are valued. CROPWAT is used to estimate evapotranspiration. The PROMETHEE model was used with five criteria: land acquisition; annuity of net present value; management effort, market uncertainty and environmental impact. In order to taking into account the preferences (weights assigned to each criterion on a scale 0-10) of decision-makers, a workshop was performed with systematized technical information. The results show conflicts between alternatives. Eucalyptus is the best alternative and alfalfa is the worst (33ha versus 75 ha) for the land acquisition criterion. Moreover, Alfalfa is the best and Poplar is the worst alternative (versus 11mil versus -193mil) for the economic criterion. For the criteria: management effort and environmental impacts, Eucalyptus and Poplar are better while Wheat - corn is the worst alternative. For market uncertainty, wheat-corn are the best alternative while Eucalyptus the worst. In the interaction with the decision makers, they take into account the five criteria. They give highest weight to land acquisition criterion (μ=8.75 and σ=1.83) and the lowest weight to environmental impact (μ=5.75 and σ=1,98). The selected alternative is Eucalyptus. Only two of eight decisionmakers show some conflict, competing Eucaliptus with Poplar, or Alfalfa in the ranking.